BRAF screening as a low-cost effective strategy for simplifying HNPCC genetic testing. Issue 9 (1st September 2004) - Domingo, E; Laiho, P; Ollikainen, M; Pinto, M; Wang, L; French, A J; Westra, J; Frebourg, T; Espín, E; Armengol, M; Hamelin, R; Yamamoto, H; et al.
Abstract : Background: According to the international criteria for hereditary non-polyposis colorectal cancer (HNPCC) diagnostics, cancer patients with a family history or early onset of colorectal tumours showing high microsatellite instability (MSI-H) should receive genetic counselling and be offered testing for germline mutations in DNA repair genes, mainly MLH1 and MSH2. Recently, an oncogenic V600E hotspot mutation within BRAF, a kinase encoding gene from the RAS/RAF/MAPK pathway, has been found to be associated with sporadic MSI-H colon cancer, but its association with HNPCC remains to be further clarified. Methods: BRAF-V600E mutations were analysed by automatic sequencing in colorectal cancers from 206 sporadic cases with MSI-H and 111 HNPCC cases with known germline mutations in MLH1 and MSH2. In addition, 45 HNPCC cases showing abnormal immunostaining for MSH2 were also analysed. Results: The BRAF-V600E hotspot mutation was found in 40% (82/206) of the sporadic MSI-H tumours analysed but in none of the 111 tested HNPCC tumours or in the 45 cases showing abnormal MSH2 immunostaining. Conclusions: Detection of the V600E mutation in a colorectal MSI-H tumour argues against the presence of a germline mutation in either the MLH1 or MSH2 gene. Therefore, screening of these mismatch repair (MMR) genes can be avoided in cases positive for V600E if no other significant evidence, such as fulfilment of the strict Amsterdam criteria, suggests MMR associated HNPCC. In this context, mutation analysis of the BRAF hotspot is a reliable, fast, and low cost strategy which simplifies genetic testing for HNPCC.